Why are structured data different? Relating differences in data representation to the rationale of OpenSDE. - Los, Renske K. (Medical informatics and the intrenet in medicine :an international journal of information processing in health care.)
OpenSDE is an application that supports clinicians with structured recording of narrative patient data to enable use of data in both clinical practice and research. OpenSDE is based on a rationale and requirements for structured data entry. In this study, we analyse the impact of the rationale and the requirements on data representation using OpenSDE. Three paediatricians transcribed 20 paper patient records using OpenSDE. The transcribed records were compared; the findings that were the same in content but differed in representation (e.g. recorded as free text instead of in a structured manner) were categorized in one of three categories of difference in representation. The transcribed records contained 1764 findings in total. The medical content of 302 of these findings was represented differently by at least one clinician and was thus included in this study. In OpenSDE, clinicians are free to determine the degree of detail at which patient data are described. This flexibility accounts for 87% of the differences in data representation. Thirteen per cent of the differences are due to clinicians interpreting and translating phrases from the source text and transcribing these to (different) concepts in OpenSDE. The differences in data representation largely result from initial design decisions for OpenSDE.